The correlation between interleukin-4 (IL-4) and programmed cell death-ligand 2 (PD-L2) expression with clinicopathological characteristics on prostate cancer - Prakoso, Ragil Unggul; Danarto, Raden; Soerohardjo, Indrawarman; Dany, Yurisal Akhmad; Dwianingsih, Ery Kus (Published by Universitas Gadjah Mada, 2024)
Prostate cancer (PCa) is the most frequent cancer diagnosed worldwide and the second most common malignancy in men. IL-4 is one of cytokines related to the inflammation process. An increase level of IL-4 in patients with PCa might be related to progression to castrate-resistance prostate cancer. Programmedcell death-ligand 2 (PD-L2) plays an important role in the anti-tumor immune system, however the exact mechanism is not fully understood. This study aimed to investigate the correlation between IL-4 and PD-L2 expression with the clinicopathological characteristic of PCa. The IL-4 and PD-L2 examinations wereperformed using quantitative real-time polymerase chain reaction (qRT-PCR) while clinicopathological characteristics were described by the Gleason score and International Society of Urological Pathology (ISUP) grade. Data collected were then analyzed using Pearson and Spearman test. In total, 20 patients withPCa tissue were collected between 2015 and 2020. The mean level of IL-4 and PDL2 were higher in metastatic PCa/M-PCa (105.64 and 665.42 ng/mL) compared to non-metastatic PCa/NM-PCa (41.62 and 215.06 ng/mL). A significant difference with medium correlation between IL-4 and PD-L2 with Gleason score and ISUPgrade was observed on all samples (p = 0.035 and 0.045; r = 0.454 and 0.473). However, no significant difference with weak correlation was observed on each group (p = 0.136 and 0.858; r = 0.065 and 0.506). Interestingly, there was a significant difference with very strong correlation observed between IL-4 andPD-L2, both on all samples (p = 0.001; r = 0.955) and on each group (p = 0.001 and 0.001; r = 0.917 and 0.955). In conclusion, there is a correlation between IL-4 and PD-L2 with the clinicopathological characteristics of PCa.